THE FALL OF PRESIDENT MUHAMMED HOSNI MUBARAK AND THE PROSPECTS FOR DEMOCRATIZATION IN EGYPT - Khasyiin, Nuril (Universitas Islam Negeri Antasari Banjarmasin, 2019)
This study discusses fall of the Mubarak regime by looking the factors and analyze how the authoritarian regime change toward democracy. January 25, became a real effort to realize that dream. This study begins with a discussion; efforts in seeking Mubarak legitimacy to support his power from Sadat's opposition, and continued with the factors that led Mubarak’s support, moved to be opposition. It’s describes the end of Mubarak regime. His Opposition from the middle class, lower class and some upper class (military). They are became a major actor in fall of the Mubarak regime. Mubarak's regime is dominated by the ruling classes in cooperation with employers in taking the natural resources of Egypt. Upper-class diversion such as corruption, electoral manipulation, arrest opposition parties and human rights abuses became commonplace in this regime. Employers in this regime to explore the economic resources. After the economic crisis, these classes subordinan then rose up against the dominant classes. This study uses a theoretical approach (replacement and legitimacy). With this both theoreticals approach will help the authors provide a powerful explanation of the fact that the field has been meticulous writer. Hepotesa of this study was Mubarak's supporters will move into the opposition, if their interests and needs are not met anymore. Mubarak attitude change employers are more concerned with the prosperity of the public, abuse of power by officers, with the pressure of economic crisis, will force the opposition to end with this authoritarian regime. Keywords: Egypt, Authoritarian Regime, Economic Crisis, Regime Change, Fall Mubarak.